Materials for the study of Āryaveda, Dharmapāla, and Candrakīrti : the Catuḥśataka of Āryadeva, chapters XII and XIII with the commentaries of Dharmapāla and Candrakīrti : introduction, translation, notes, Sanskrit, Tibetan and Chinese texts, indexes - Tillemans, Tom J. F. (Motilal Banarsidass Publishers, 2008)
Study of Catuḥśataka with commentaries, work on Mādhyamika Buddhism.